Theoretical and Experimental Study of the Pounding Response for Adjacent Inelastic MDOF Structures Based on Dimensional Analysis - Qiaoyun Wu; Ziliang Liu; Tao Wang; Xuyong Chen (Shock and Vibration)
Dimensional analysis is applied to study the pounding response of two inelastic multidegree of freedom (MDOF) structures under simplified earthquake excitation. The forces and deformations of the collision processes are simulated by adopting the improved Kelvin pounding model. The inelastic characteristics of MDOF structures are described by the bilinear interstory resistance model, and the representations of dimensionless impact force and the dimensionless motion equation in the pounding process are derived. On the basis of the above-mentioned theoretical deduction, the superiority of the improved Kelvin model is verified by comparing the impact response of the improved Kelvin model and the Kelvin model. Finally, the validity of the proposed theoretical method is further proved by the comparison between results from the shaking table tests of adjacent four-story and three-story steel frame structures and the corresponding numerical results obtained by the MATLAB program.